Increased Risk of Venous Thromboembolism in Patients With Amyotrophic Lateral Sclerosis: Results From a US Insurance Claims Database Study. Issue 1 (19th February 2023) - Kupelian, Varant; Viscidi, Emma; Hall, Susan; Li, Li; Eaton, Susan; Dilley, Anne; Currier, Nicolas; Ferguson, Toby; Fanning, Laura
Abstract : Background and Objectives: Reduced mobility in patients with amyotrophic lateral sclerosis (ALS) is hypothesized to increase the risk of venous thromboembolism (VTE). A few small, single-center studies have investigated the risk of VTE in patients with ALS. Given the high morbidity and mortality associated with VTE, further understanding of the risk in patients with ALS may inform clinical care. The objective of this study was to investigate the incidence of VTE in patients with ALS compared with controls without ALS. Methods: Patients were identified from a US health insurance claims database, Optum's deidentified Clinformatics Data Mart Database, between 2004 and 2019. ALS cases were defined as patients aged 18 years or older with (1) 2 or more ALS claims at least 27 days apart including at least 1 claim from a neurologist visit or (2) 1 or more ALS claims and a prescription for riluzole or edaravone. Each ALS case was matched on age and sex to 5 controls without ALS. VTE was defined as at least 1 claim for VTE and at least 1 anticoagulant prescription or VTE-related procedure within 7 days before and 30 days after a VTE claim date. Incidence rates were reported per 1, 000 person-years. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using the Cox proportional hazards model. Results: Among 4, 205 ALS cases and 21, 025 controls, incident VTE occurred in 132 ALS cases (3.1%) and 244 controls (1.2%). Incidence rates of VTE were 19.9 per 1, 000 person-years (95% CI 16.7–23.6) in ALS cases compared with 6.0 per 1, 000 person-years (95% CI 5.0–7.1) in controls. ALS cases were about 3 times more likely to develop VTE (HR 3.3, 95% CI 2.6–4.0), with similar results among men and women. The median time to first VTE was 10 months from the initial ALS claim in ALS cases. Discussion: Consistent with previous smaller studies, a higher incidence rate of VTE was observed in a large sample of patients with ALS from across the United States, as compared to matched controls. The markedly increased risk underscores the importance of preventive efforts and careful monitoring for VTE in patients with ALS and may have implications for the management of ALS.